2023
DOI: 10.1039/d3tb00541k
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-assisted albumin-based biomineralization nanocarriers with NIR-II-targeted photothermal performance towards broad-spectrum radical scavenging

Abstract: Oxidative stress is a state of imbalance in the body's oxidative balance, which can cause or worsen many diseases. Much of the study focuses on the direct scavenging of free...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Natural polyphenols with abundant phenolic hydroxyl groups have attracted extensive attention in constructing multienzyme-like platforms due to their antioxidative activities, exceptional biocompatibility, metal chelating properties, and universal adherent affinity. Especially, polyphenols could coordinate with multiple metal ions to form metal–phenolic networks (MPNs) to integrate the advantages of the two components for the rational design of diverse MPNs-based materials for biomedical applications. , Meanwhile, benefiting from their numerous properties, we have demonstrated that the MPNs are suitable as building blocks for constructing multienzyme-like nanomaterials with tunable enzyme-mimetic activities. , …”
Section: Introductionmentioning
confidence: 99%
“…Natural polyphenols with abundant phenolic hydroxyl groups have attracted extensive attention in constructing multienzyme-like platforms due to their antioxidative activities, exceptional biocompatibility, metal chelating properties, and universal adherent affinity. Especially, polyphenols could coordinate with multiple metal ions to form metal–phenolic networks (MPNs) to integrate the advantages of the two components for the rational design of diverse MPNs-based materials for biomedical applications. , Meanwhile, benefiting from their numerous properties, we have demonstrated that the MPNs are suitable as building blocks for constructing multienzyme-like nanomaterials with tunable enzyme-mimetic activities. , …”
Section: Introductionmentioning
confidence: 99%